The Influence of Social Media and Brand Image on Purchase Decisions Through Consumer Motivation at Ikat Weaving CV Silvi MN Paradila Lamongan - Evi Ariani Auzia; Mohammad Arief (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
In this study there are 4 variables, namely Social Media, Brand Image, Purchase Decision, and Consumer Motivation as a Mediation or Intervening variable. This study uses quantitative methods with the number of respondents as many as 97 people. The purpose of this study was to determine the effect of social media and brand image on purchasing decisions through consumer motivation on ikat weaving CV Silvi MN Paradila Lamongan. The results of this study are (1) Social media variables have a positive and significant effect on purchasing decisions with a significant level of 0.044 0.05 (2) Brand image variables have a positive and significant effect of 2.213 on purchasing decisions with a significant level of 0.029 0.05 (3) Social media variable has a positive and significant effect of 4.712 on consumer motivation with a significant level of 0.000 0.05 (4) Brand image variable has a positive and significant effect of 4.256 on consumer motivation with a significant value of 0.000 0.05 (5) Variable consumer motivation has a positive and significant effect of 4.712 on purchasing decisions with a significant value of 0.000 0.05 (6) Social media variables have a positive and significant effect of 0.0384 on purchasing decisions through consumer motivation as a mediating or intervening variable (7) Brand image variable has a positive and significant effect fish of 0.0265 to purchasing decisions through consumer motivation as a mediating or intervening variable